1992
DOI: 10.1113/jphysiol.1992.sp019073
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclic nucleotides and calcium in the nutrient‐induced release of cholecystokinin‐like immunoreactivity in rats.

Abstract: SUMMARY1. This study was undertaken with an isolated vascularly perfused rat duodenojejunal preparation to investigate the mechanisms of the release of cholecystokinin measured by immunoassay (cholecystokinin-like immunoreactivity, CCK-LI).2. Intra-arterial infusion of forskolin (2-20 /1M) evoked a prompt and wellsustained secretion of CCK-LI which was increased to a mean value of 600 % of basal with the highest dose tested. 3-Isobutyl-1-methylxanthine (IBMX) (10-6-10-M) stimulated the secretion of CCK-LI (max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Administration of calcium channel blockers strongly reduced the bombesin-induced release of gastrin in the isolated vascularly perfused stomach preparation (Guo, Thompson & Singh, 1988). Similarly, the cholecystokinin secretion was strongly dependent on calcium in the isolated vascularly perfused rat duodenojejunum preparation since calcium channel blockers of the phenylalkylamine and dihydropyridine families reduced the peptone-induced cholecystokinin secretion (Cuber, Aucouturier, Bernard & Chayvialle, 1992). The same compounds, perfused in the present study at the same concentrations as in that previous report, were unable to reduce the glucose-evoked NTLI secretion.…”
Section: Discussionmentioning
confidence: 93%
“…Administration of calcium channel blockers strongly reduced the bombesin-induced release of gastrin in the isolated vascularly perfused stomach preparation (Guo, Thompson & Singh, 1988). Similarly, the cholecystokinin secretion was strongly dependent on calcium in the isolated vascularly perfused rat duodenojejunum preparation since calcium channel blockers of the phenylalkylamine and dihydropyridine families reduced the peptone-induced cholecystokinin secretion (Cuber, Aucouturier, Bernard & Chayvialle, 1992). The same compounds, perfused in the present study at the same concentrations as in that previous report, were unable to reduce the glucose-evoked NTLI secretion.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, vascularly perfused EGTA abolished the CCK response to peptones, whereas complexing luminal calcium by infusing EGTA into the duodenum had no effect (36). Additionally, peptone induced CCK secretion was strongly reduced upon intraarterial infusion of blockers of L-type Ca 2ϩ channels (36). To further test the hypothesis that intracellular Ca 2ϩ is required for CCK secretion, we incubated the STC-1 cells with BAPTA-AM and peptone or CPX.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to these putative effectors, it was recently shown that rab3 interacts in a Ca 2+ ‐dependent manner with calmodulin to regulate exocytosis [35,40]. As bombesin and protein hydrolysates, potent stimulants of CCK release in I‐cells [2] and in STC‐1 cells [23] require intracellular calcium to exert their effect. An attractive hypothesis could be the formation of a rab3A‐Ca 2+ /calmodulin complex, which could contribute to a fine tuning of CKK exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystokinin (CCK) exerts important actions in the digestive tract [1]. Agonist‐induced stimulation of CCK release from intestinal endocrine I‐cells is achieved through activation of protein kinase A and C, and of calcium channels [2,3]. This was observed as well in the enteroendocrine cell line STC‐1 [4,5], in which the role of the extracellular signal‐regulated kinase (ERK)1/ERK2 transduction pathway and of SNARE (soluble N ‐ethylmaleimide‐sensitive factor attachment protein receptor) proteins in the control of CCK release was demonstrated [6,7].…”
Section: Introductionmentioning
confidence: 99%